The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1002/1097-0142(20000801)89:3<482::aid-cncr2>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostained cathepsins B and L correlate with depth of invasion and different metastatic pathways in early stage gastric carcinoma

Abstract: Tumors with overexpression of cathepsins have powerful potential for invasiveness in the early stage of gastric carcinoma. Moreover, the authors hypothesize that cathepsins may be one of the determinants of the metastatic route. To the authors' knowledge, this is the first report on specific proteases concerning the mode of metastasis, and the results of this study suggest that therapeutic strategies for early stage gastric carcinoma might need to be changed according to the status of cathepsins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Procathepsin‐L secreted by the INSL3 transfectants may itself have an important role in the formation, vascularization, and growth of these xenograft tumors. Cathepsin‐L promotes the migration and basement membrane degradation by tumor cells55, 56 and facilitates neovascularization in vivo by enhancing the proteolytic, promigratory capacity of endothelial progenitor cells 57. Thus, both INSL3 target molecules, S100A4, and procathepsin‐L, may support a microenvironment within the grafts which is conducive to rapid tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Procathepsin‐L secreted by the INSL3 transfectants may itself have an important role in the formation, vascularization, and growth of these xenograft tumors. Cathepsin‐L promotes the migration and basement membrane degradation by tumor cells55, 56 and facilitates neovascularization in vivo by enhancing the proteolytic, promigratory capacity of endothelial progenitor cells 57. Thus, both INSL3 target molecules, S100A4, and procathepsin‐L, may support a microenvironment within the grafts which is conducive to rapid tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous Cathepsin L immunohistochemistry studies have identified granular cytoplasmic staining patterns in sarcomas, oral squamous cell carcinomas, gastric cancers and gliomas 17–20. Quantitative RNA slot blot analysis has shown that kidney and testicular tumors express the highest levels of Cathepsin L compared to nonsmall cell carcinomas of the lung and many cancers including breast, ovary, colon, adrenal, bladder, prostate and thyroid cancers 21…”
Section: Discussionmentioning
confidence: 99%
“…CTSL localizes primarily to the lysosomes and is also a constituent of the nuclear protein fraction. Although previous studies have shown that CTSL is upregulated in GC and could be identified as a marker of enhanced invasiveness of GC [10,15,30], the function of nuclear CTSL in GC angiogenesis has not been determined. In this study, we found that nuclear CTSL is significantly upregulated in GC cancer and predicts poor prognosis of GC patients.…”
Section: Ctsl Expression Is Positively Correlated With Vegf-d In Gc Tmentioning
confidence: 99%